A SURVEY OF THE EXPERIENCE, KNOWLEDGE AND ATTITUDE OF DENTAL PRACTITIONERS IN BULGARIA ABOUT CHILD ABUSE AND NEGLECT - Mariana M. Dimitrova; Veselina K. Kondeva; Sevda I. Rimalovska (Peytchinski Publishing, 2021)
Aim: To study the experience, knowledge and attitude of dental practitioners in Bulgaria about child abuse and neglect. Material and methods: An anonymous questionnaire was conducted on 265 dental practitioners from several regions of Bulgaria. The questionnaire consists of 15 questions, including demographic characteristics and questions about their attitude, knowledge and actions in suspected cases of child abuse and neglect. Results: Only 1/4 of the respondents, n=60 (22.3%), reported having suspected cases of Child Abuse and Neglect, and only 5.7% of them were reported to the authorities. The notification to the relevant institutions increases with the professional experience up to 30% to 40%. The most common reason for not reporting was lack of knowledge of the way or procedures of reporting (40.4%), fear of subsequent violence against the child - 23.4% and fear of consequences for the child when the relevant institutions interfere - 12.8%. Irregular dental visits were considered the most significant indicator of neglect of children's oral health. Need for additional education and training on recognizing the signs of child abuse and neglect were reported from 72.5% of the participants. Conclusions: The present study showed uncertainty in recognizing and reporting suspected cases of child abuse and neglect, especially for the younger dentists and for those without a certain specialty. There is a clear need for additional education of dental practitioners, as well as certain legal guidelines on the procedures of reporting and recording suspected cases, along with reliable support from the relevant institutions.